The Effect of Peer-Banks on Bank Liquidity Management: The Case of Islamic Banks in Indonesia - Titi Dewi Warninda; Diamantin Rohadatul Aisy (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
This study aims to analyze the influence of peer banks on the liquidity management of Islamic banks in Indonesia and whether such influence is robust during the periods of the global financial crisis. This research uses fixed-effect panel data regression with robust standard error and the data of Islamic banks in Indonesia for the years 2007-2020. This research finds that peer-banks have a negative impact on Islamic bank liquidity, and it is robust in the global financial crisis periods. This study contributes to the policymakers and literature regarding the peer bank effect, especially in the liquidity management of Islamic banks. The liquidity management of Islamic banks is not only influenced by the conditions of the Islamic banks themselves but also affected by the behavior of other Islamic banks.